2013
DOI: 10.5539/ijbm.v8n23p30
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Literacy on New Venture Survival

Abstract: This is an investigation into the impact of financial literacy on new venture survival. A model is proposed in which increased adoption of financial tools (e.g. financial statements and financial ratios) leads to increased frequency of financial statement generation which in turn increases the likelihood of loan repayment and decreases the probability of venture failure. A structural model was then tested using data from 509 young entrepreneurs in Canada who had received start up loans through their participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
1
23

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 40 publications
9
102
1
23
Order By: Relevance
“…The preceding literature supports the assertion that there is a relationship between financial literacy, the management skills of entrepreneurs and the competitiveness of the economy (Wise, 2013;Binks et al, 2006). Therefore, over the recent past, there has been an upsurge in studies which have identified the need for financial education and literacy amongst SMEs (Fatoki, 2014;Wise, 2013;Hussain et al, 2008;Binks et al, 2006). One of the explanations offered by banks in the UK for the higher rejection rate of loan applications by SMEs is the poor preparation and provision of financial information to allow for adequate risk assessment due to information asymmetry that involves a higher diligence and monitoring cost (Deakin and Hussain, 1994).…”
Section: Literature Reviewsupporting
confidence: 55%
See 1 more Smart Citation
“…The preceding literature supports the assertion that there is a relationship between financial literacy, the management skills of entrepreneurs and the competitiveness of the economy (Wise, 2013;Binks et al, 2006). Therefore, over the recent past, there has been an upsurge in studies which have identified the need for financial education and literacy amongst SMEs (Fatoki, 2014;Wise, 2013;Hussain et al, 2008;Binks et al, 2006). One of the explanations offered by banks in the UK for the higher rejection rate of loan applications by SMEs is the poor preparation and provision of financial information to allow for adequate risk assessment due to information asymmetry that involves a higher diligence and monitoring cost (Deakin and Hussain, 1994).…”
Section: Literature Reviewsupporting
confidence: 55%
“…The preceding literature supports the assertion that there is a relationship between financial literacy, the management skills of entrepreneurs and the competitiveness of the economy (Wise, 2013;Binks et al, 2006). Therefore, over the recent past, there has been an upsurge in studies which have identified the need for financial education and literacy amongst SMEs (Fatoki, 2014;Wise, 2013;Hussain et al, 2008;Binks et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 68%
“…This is management's primary valuecreating activity-the f low of knowledge to tenant firms through their access of incubation services. In some cases, management possesses the relevant knowledge themselves, by virtue of their own prior experience as entrepreneurs dealing with the strategic and operational challenges of new venture creation (Wise [2013]). And in other cases the relevant knowledge is possessed by others, with management acting to broker that knowledge to their tenant companies by drawing up their own professional networks (Osborne [2004]; Papagiannidis et al [2009]; Warren et al [2009]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[3] conducted a study on the impact of financial literacy on firm financial service utilization. [14] assessed the level of micro entrepreneurs in South Africa. [15] present examination of rule of thumb training results on financial literacy.…”
Section: Approach Of the Reviewmentioning
confidence: 99%